DNA‐encoded plasmonic bubbles aggregating dual‐microRNA SERS signals for cancer diagnosis - Yu Yang; Hao Lu; Dan Fang; Yuyuan Zhang; Yuteng Tang; Songsong Zhao; Jun Yan; Xiaojie Qin; Jianlei Shen; Fan Yang (Aggregate)
Abstract Solid bubbles have expanded the SERS assay toolbox, but their detection performance in biofluids is still hampered by the irrational design of the plasmonic sensing interface. A plasmonic bubble aggregate‐driven DNA‐encoded SERS assay is reported here that enables simultaneous, ultrasensitive, and specific detection of multiple miRNAs in blood samples for accurate cancer diagnosis. In this assay, the buoyancy of plasmonic bubbles allows them to self‐aggregate at a droplet apex for SERS reconfiguration, form single‐layer bubble aggregates with plasmonic nanogaps, and prevent the coffee ring effect during evaporation assembly. Furthermore, DNA‐encoded plasmonic bubbles seamlessly couple with dual‐color catalytic hybridization assembly to amplify the specific miRNA‐responsive Raman signal, and function as both an analyte concentrator and a Raman signal aggregator without external forces. Using these merits, this magnet‐free, portable assay achieves femtomolar dual‐miRNA quantitation with single‐base resolution, simultaneous miRNA detection across four cell lines, and accurate cancer diagnosis (AUC = 1) via analyzing 40 blood samples with machine learning, thus providing a promising tool for clinical diagnosis.